2007
DOI: 10.1203/pdr.0b013e3180a725b1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caffeine on the Preterm Sheep Ductus Arteriosus

Abstract: Caffeine and other methyl xanthines are widely used in the neonatal period. A recent, randomized, placebo-controlled, multicenter trial found that infants who were randomly assigned to caffeine treatment had less need for pharmacologic and/or surgical closure of a patent ductus arteriosus (PDA). We hypothesized that the decreased need for pharmacologic and surgical closure of the PDA after caffeine treatment might be due to a direct effect of caffeine on ductus contractility. We examined preterm fetal lamb duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…Our findings are consistent with those of a recent study demonstrating that, in isolated DA from fetal sheep, caffeine had no direct effect on vessel contractility (33). The temporal changes in PBF and DA blood flow we observed are consistent with our previous studies, which have shown that immediately after birth retrograde flow (left-to-right shunting) through the DA contributes to the increase in PBF.…”
Section: Effects Of Caffeine On Preterm Lambssupporting
confidence: 93%
“…Our findings are consistent with those of a recent study demonstrating that, in isolated DA from fetal sheep, caffeine had no direct effect on vessel contractility (33). The temporal changes in PBF and DA blood flow we observed are consistent with our previous studies, which have shown that immediately after birth retrograde flow (left-to-right shunting) through the DA contributes to the increase in PBF.…”
Section: Effects Of Caffeine On Preterm Lambssupporting
confidence: 93%
“…27,28 Our findings are analogous to improved pulmonary status and lesser need for PDA treatment in infants treated with early caffeine treatment, 29 where no direct effect of caffeine on periductal ductal smooth muscle constriction was demonstrable. 30 The primary weaknesses of this study were the small sample size, open label design and high rate of PDAs in the beractant group. This is a highly selected population of very premature infants who were mechanically ventilated for RDS, infants with the greatest risk of developing the morbidities of prematurity, including PDAs and chronic lung disease.…”
Section: Discussionmentioning
confidence: 93%
“…Although caffeine may also affect several signaling molecules involved in ductal constriction, investigations on this effect are still inconclusive. [24][25][26] Possibly, improved respiratory morbidity in the neonate reduces the likelihood of a PDA requiring treatment, although the management of pharmacological and surgical ductal closure remains a controversial area of practice. 27 The physiologic effects of caffeine may increase the success of early initial continuous positive airway pressure therapy or facilitate weaning from the ventilator and result in a reduction of endotracheal ventilation and protection against associated lung injury.…”
Section: Discussionmentioning
confidence: 99%